Excellence in Education and Strategic Promotion in Strengthening the Image of SDN Ekologi Kahuripan Pajajaran through 7P Integration - Rika Aryanti; Danny Meirawan; Taufani C Kurniatun; Eka Prihatin (Papanda Publisher, 2026)
Abstract This study aims to analyze the strengthening of school image through the integration of the marketing mix of educational services (7P) by linking program excellence and strategic promotion. The study was carried out at SDN Ecology Kahuripan Pajajaran, Purwakarta Regency, West Java, Indonesia. The approach used is qualitative descriptive with a case study design with phenomenological elements. Primary data was obtained from school principals, teachers, education staff, students, and parents/committee representatives; Secondary data comes from school profiles, vision-mission, program archives, and promotional media. Data collection was carried out through semi-structured interviews, observation of learning activities and the physical environment, as well as documentation; The research instrument includes interview guidelines, observation sheets, and document checklists. Data analysis uses the Miles and Huberman interactive model (reduction, presentation, verification), while the validity of the data is maintained through triangulation of sources, member checking, and peer debriefing. The findings show that all elements of the 7P are mutually reinforcing: ecological character programs as a differentiation (product), BOS-based non-levied education (price), large land as a natural laboratory (place), digital promotion and parent networking (promotion), leadership and example of teachers as brand agents (people), consistent branding process (process), and physical evidence of facilities and student work (physical evidence). It was concluded that the image of the school was formed mainly from the consistency of the service experience, not just promotion. The implication is that image management needs to be positioned as an integrated service system. It is recommended to strengthen periodic evaluations, website optimization, and facility sustainability strategies as well as non-levy funding mitigation. continuously in school.